THE EFFECT OF GIVING DRAGON FRUIT PEEL JUICE ON THE PRODUCTION OF 10 WEEKS OF QUAIL CARCASS - I P. A. Y., Putra; Dewi, G. A. M. K.; Wirapartha, M. (Jurnal Peternakan Tropika; Vol 9 No 2 (2021): Vol. 9 No. 2 Tahun 2021; May - August, 2021)
This study aims to determine the production of quail carcasses aged 10 weeks given dragon fruit peel juice. This research was conducted in January 2021 at Mr. Anwar House, Pasraman Unud Housing, Blok F-30 and Poultry Laboratory, Faculty of Animal Husbandry, Udayana University. The design used a completely randomized design (CRD) with four treatments and four replications. The four treatments were: water without dragon fruit peel juice or control (P0), drinking water given dragon fruit peel juice as much as 1% (P1), 2% (P2), and 3% (P3). The variables observed were cut weight, carcass weight, carcass percentage and carcass weight part (chest, back, wings, thighs). The results of giving dragon fruit peel juice in this study showed that the cut weight, carcass weight, carcass percentage and carcass weight part (chest, back, wings, thighs) were not significantly different (P> 0,05) on addition of dragon fruit peel juice 1%, 2% and 3% . The conclusion of this study shows that giving dragon fruit peel juice (Hylocereus polyrhizus) with a concentration of 1%, 2% and 3% in drinking water has no effect on cut weight, carcass weight, carcass percentage, and carcass weight part (chest, back, wings, thigh) 10 week old Coturnix-coturnix japonica quail.     Keywords:   Coturnix-coturnix japonica quail, carcass production , carcass weight part, dragon fruit skin (Hylocereus polyrhizus)